The partisan politics of law and order - Wenzelburger, Georg (Studies in crime and public policy, 2020)
The comparative study of law and order policies has mostly overlooked partisan politics as a possible explanation of differences between Western nations. Filling this gap in the literature, this book argues theoretically and substantiates empirically that law and order policies are heavily affected by partisan politics. By means of a large-N analysis of spending data and a new dataset on law and order legislation as well as four in-depth case studies, the empirical evidence shows that party competition and the party ideology of governments do affect policies-depending on the institutional context of a political system. Moreover, path dependencies tend to freeze these effects over a certain period of time creating positive feedback dynamics.